melanigutierrez93
melanigutierrez93
02-07-2020
Mathematics
contestada
Solve: g^2x + 1 = g^3x – 2
Respuesta :
Tucon
Tucon
03-07-2020
[tex]\displaystyle\bf\\g^{2x+1}=g^{3x-2}\\\\g=g\\\\3x-2=2x+1\\\\3x-2x=1+2\\\\\boxed{\bf x=3}[/tex]
Answer Link
VER TODAS LAS RESPUESTAS ( 51+ )
Otras preguntas
What is likely to happen in the long run to firms that do not reach minimum?
Art historians have asserted that van gogh s work was the epitome of postimpressionism. true false
Some South Vietnamese aided the Vietcong in their struggle to overthrow the government. True False
how many moles of hydrogen are in 2.8 moles of caffeine
Which cell structure is responsible for breaking down sugar molecules in order to supply energy to the cell?
What is the What is the overall reaction order for this rate law: rate= k[A][B]? overall reaction order for this rate law: rate= k[A][B]?
what is non-violent resistance
How would you explain American values to someone who has no idea about our society?
How many constitutions has Texas had? A.9 B.8 C.5 D.15
Which of the following substances dissolves most readily in gasoline? A. CH4 B. HC1 C. NH3 D. NaBr